1998
DOI: 10.1111/j.1945-5100.1998.tb01604.x
|View full text |Cite
|
Sign up to set email alerts
|

The crystalline lunar spherules: Their formation and implications for the origin of meteoritic chondrules

Abstract: Abstract-Crystalline lunar spherules (CLS) from three thin sections of Apollo 14 regolith breccias (143 18,6; 14318,48 and 14315,20) have been examined. The objects have been classified and their abundances, size distributions, bulk compositions, and (where possible) plagioclase compositions determined. By number, 64% consist predominantly of very tine-grained equant plagioclase grains but can also contain larger (-50 pm) feldspar crystals (type X), while 22% contain plagioclase lathes in a fine-grained mafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…It is reasonable to ask whether FeO/MnO variability among the chondrules results from a difference in volatility between Fe and Mn leading to differing fractional losses of each element from the chondrules as molten droplets. However, comparison of FeO/MnO for the chondrules to similar data for impact-melted lunar crystalline spherules (Symes et al, 1998;Ruzicka el al., 2000) suggests that volatility-driven fractionation of the Fe/Mn ratio during impact melting is unlikely. Symes et al (1998) reported the compositions of crystalline lunar spherules (CLSs) extracted from Apollo 14 breccias 143 15 and 14318.…”
Section: Chondrule Selection and Analysis By Instrumental Neutron Actmentioning
confidence: 72%
See 1 more Smart Citation
“…It is reasonable to ask whether FeO/MnO variability among the chondrules results from a difference in volatility between Fe and Mn leading to differing fractional losses of each element from the chondrules as molten droplets. However, comparison of FeO/MnO for the chondrules to similar data for impact-melted lunar crystalline spherules (Symes et al, 1998;Ruzicka el al., 2000) suggests that volatility-driven fractionation of the Fe/Mn ratio during impact melting is unlikely. Symes et al (1998) reported the compositions of crystalline lunar spherules (CLSs) extracted from Apollo 14 breccias 143 15 and 14318.…”
Section: Chondrule Selection and Analysis By Instrumental Neutron Actmentioning
confidence: 72%
“…However, comparison of FeO/MnO for the chondrules to similar data for impact-melted lunar crystalline spherules (Symes et al, 1998;Ruzicka el al., 2000) suggests that volatility-driven fractionation of the Fe/Mn ratio during impact melting is unlikely. Symes et al (1998) reported the compositions of crystalline lunar spherules (CLSs) extracted from Apollo 14 breccias 143 15 and 14318. The FeO/MnO ratios for two groups of seven spherules each were tightly grouped at 67 ?…”
Section: Chondrule Selection and Analysis By Instrumental Neutron Actmentioning
confidence: 72%
“…In our context, it is noteworthy that D. Sears (University of Arkansas) envisions a chondrule forming process related to impact processes. He argues that chondrules formed on asteroids during an impact by a larger body (Symes et al 1998). Our impact "chondrules" were not formed in zero gravity but in an equally turbulent, fiery cloud of rock and melt particles.…”
Section: Discussion-depositional Environment Of Yax-1 Impactitesmentioning
confidence: 99%
“…Crystalline lunar spherules, with physical properties similar to meteoritic chondrules but with highland compositions, are common at the Apollo 14 site that is thought to contain ejecta from the Imbrium impact. Thus, impact spherules take on the structural properties of chondrules only when the impact is sufficiently large in relation to the size of the target body and flight times are long enough for extensive crystallization (Symes et al, 1998). Only on asteroids that have experienced impacts large enough to produce craters with radii comparable to the radius of the asteroid would one expect the proportion of chondrules to melt spherules and agglutinates to be high.…”
Section: Premise Iv: Chondrules Were Formed By Impact Into a Regolithmentioning
confidence: 99%
“…However, we have previously suggested that gravitational perturbations by Jupiter might mean that impacts sufficient to create chondrules occur preferentially near resonances (Symes et al, 1998).…”
Section: Premise Iv: Chondrules Were Formed By Impact Into a Regolithmentioning
confidence: 99%